Celiac disease in children - diagnosis in light of the current 2020 ESPGHAN guidelines - Sochal, Piotr; Iwaszko-Sochal, Klaudyna; Szczepaniak-Wójtowicz, Elżbieta (Journal of Education, Health and Sport, 2023)
Celiac disease is a chronic immune disorder of the small intestine that is triggered by the consumption of gluten in genetically predisposed individuals. The disease is difficult to diagnose and treat, and its incidence is increasing. It can have different symptoms and clinical manifestations in individuals. Diagnosis is usually based on the presence of specific antibodies and histopathological examination of biopsy specimens from the small intestine. The only effective treatment is a gluten-free diet for life. Diagnosis of celiac disease in children is mainly based on the presence of specific an- tibodies in the blood, such as antibodies to tissue transglutaminase (tTG), antibodies to endomysium (EMA) or deamidated gliadin peptides (DGP). In addition, genetic testing is also used in diagnosis to detect the presence of HLA DQ2 or DQ8 genes, which are often present in people with celiac disease. The final diagnosis of celiac disease is based on a combination of the results of these tests and the presence of characteristic lesions in the small intestine, which are detected during endoscopy and small bowel biopsy.